2018
DOI: 10.1007/978-1-4939-7595-2_26
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Highly Selective MMP Antibody Inhibitors

Abstract: Inhibiting individual MMPs of biomedical importance with high selectivity is critical for both fundamental research and therapeutic development. Here we describe the methods for discovery of inhibitory monoclonal antibodies from synthetic human antibody phage display libraries carrying convex paratopes encoded by long complementarity-determining region (CDR)-H3 segments. We demonstrate the application of this technique for isolation of highly specific and potent antibody inhibitors of human MMP-14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…As previously mentioned, monoclonal antibodies [120] are also among several additional experimental MMP/ADAMs inhibitors undergoing pre-clinical testing in various inflammatory disorders and cancer. These include, MMP-14 [121], MMP-9 [122], and, ADAM17 [123].…”
Section: In Vitro Cell Cultures Appear To Be Integral For Assessing the Action Of Mmp Inhibitorsmentioning
confidence: 99%
“…As previously mentioned, monoclonal antibodies [120] are also among several additional experimental MMP/ADAMs inhibitors undergoing pre-clinical testing in various inflammatory disorders and cancer. These include, MMP-14 [121], MMP-9 [122], and, ADAM17 [123].…”
Section: In Vitro Cell Cultures Appear To Be Integral For Assessing the Action Of Mmp Inhibitorsmentioning
confidence: 99%
“…We have used several strategies to identify specific inhibitory antibodies of uPA. Based on previously identified potent antibody inhibitors against serine proteases [26,27], and matrix metallopeptidases (MMPs) [12], where the main driver of inhibition is the long CDRH3 loop inserted into the protease active site [27,28], we designed a set of synthetic antibody libraries based on the long CDRH3 loops of two potent MTSP-1 inhibitory Fabs (Unpublished results). Several uPA antibodies were identified using these biased antibody libraries but none showed an inhibitory effect, and some behaved as substrates of urokinase ( Figure Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Our results for protease production and identification of rAbs to MT-SP1 (aka, matriptase), and urokinase plasminogen activator (uPA) showed that conformationally selective inhibitory antibodies can be identified from a naïve human Fab library displayed on bacteriophage. Several inhibitory antibodies have been developed to other proteases including HGFA [10], Factor XIa [11], MMP9 [12] and β-tryptase [13]. Another advantage of rAbs is that the antibody sequence of the binder allows for in vitro affinity maturation, mimicking an immune response, to select Abs with higher affinity and lower off-rate [14].…”
Section: Introductionmentioning
confidence: 99%
“…A monoclonal antibody against MMP-14 selectively blocks proMMP-2 activation which is required for lymphangiogenesis in vitro and ex vivo [ 443 ]. In preclinical models, several monoclonal antibodies against MMP-9 [ 444 , 445 ] and MMP-14 [ 446 ] initially appeared promising, but the generation of highly selective MMP antibody inhibitors remains a desideratum [ 447 ]. Phage display library-derived peptides against the MT loop of MMP-14, such as HS7, which may be useful in the early diagnosis of tumors and for the development of peptide-mediated drugs [ 448 ].…”
Section: Translational Assessment and Future Prospectmentioning
confidence: 99%